Program 11 Clean in an Effort to Habituate Caring for the School Environment to Strengthen P5 in Madrasah Ibtidaiyah - Agung Widodo; Fatchurohman Fatchurohman; Azmi Tsani Hasona; Muhammad Maskur Musa; Razie Bin Nasarruddin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan IAIN Manado, 2023)
The educational process is, of course, influenced by various parties, one of which is the environment. The relationship between the two cannot be separated. Today, it is often found that there are many environmental problems. This happens because of human activity itself; most people nowadays tend to be more concerned with their own needs without thinking about the impact on other people or the environment. The purpose of this study is to explain the Clean 11 program in an effort to cultivate a caring attitude towards the school environment and strengthen P5 at MIS NU Al-Utsmani. This type of research was conducted using field research methods with a qualitative, descriptive approach. The data collection technique uses observation, interviews, and documentation. The results of this study show that the